2022
DOI: 10.15407/hftp13.03.259
|View full text |Cite
|
Sign up to set email alerts
|

Platinum-containing carbon nanostructures for the creation of electrically conductive ceramics using 3D printing of CJP technology

Abstract: Carbon nanostructures (CNS) were synthesized by the electric arc plasma chemical method during the evaporation of a high-quality graphite electrode of the brand “fine-grained dense graphite” (FGDG-7) filled with a catalyst (Pt), which was evaporated in a helium environment. In the synthesis process, the following were synthesized: multi-walled (MWCNT) and single-walled carbon nanotubes (SWCNT), fullerenes, graphene packets and nanocomposites. A deposit in the form of growth on the cathode electrode was also sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In the results of the research, a tendency to increase the strength characteristics of 3D-products can be observed when using CNS as a filler of the supporting matrix (Figs. 23,24). Вміст ВНТ %об…”
Section: Research Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the results of the research, a tendency to increase the strength characteristics of 3D-products can be observed when using CNS as a filler of the supporting matrix (Figs. 23,24). Вміст ВНТ %об…”
Section: Research Resultsmentioning
confidence: 99%
“…Such and similar nanomaterials can play the role of fillers for the creation of modern composites [20][21][22][23], which is already being studied for 3D printing technologies [24][25][26][27]. Such materials make it possible to create modern and advanced materials in the field of promising sorbents [28][29][30][31][32][33][34][35][36], biological materials [37][38][39][40][41][42], fuel cells [43][44][45][46], solar panels [47][48][49], and much more.…”
Section: Introductionmentioning
confidence: 99%
“…and 2 1    . With such replacements, the first equation in (24) transforms into the second and vice versa. We are interested in the first solution…”
Section: Free and Internal Configurational Energy Equations Of Thermo...mentioning
confidence: 99%
“…KDP nanocrystals and carbon nanostructures (fullerenes [1-4], fullerites [5], endofullerins [6], graphenes [7][8], nanotubes [9][10]) with various synthesis methods [11][12][13][14][15][16][17][18][19] can be used as fillers for creating new composites [20][21][22][23] suitable for 3D printing technology [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Mesoporous material refers to a kind of porous material with a pore diameter of 2-50 nm with the characteristics of extremely high specific surface area, regular and orderly pore structure, narrow pore size distribution and continuously adjustable pore size [1]. Its preponderant characteristics in photology, electricity, thermology, mechanics and catalysis make it widely used in the fields of fine ceramics [2], microelectronics [3], chemical engineering [4], bioengineering and medicine [5,6]. The research and application of mesoporous materials in pharmaceutical field, especially in nano-drug delivery systems (NDDSs), has attracted extensive attention and developed rapidly.…”
Section: Introductionmentioning
confidence: 99%